Compost produced by solid state bioconversion of biosolids: a potential resource for plant growth and environmental friendly disposa - Molla , Abul Hossain; Fakhru’l-Razi, Ahmadun; Hanaﬁ, Mohamed Musa; Alam, Md. Zahangir (Taylor & Francis, 2005)
Compost produced by solid-state bioconversion of the Indah Water Konsortium domestic wastewater treatment plant’s sludge/biosolids significantly influenced the plant growth and development of corn (Zea mays). The solid-state bioconversion refers to the control growth of microorganisms, generally on the surface of water-insoluble substances for biodegradation of biopolymers and bioremediation of chemical compounds. Compost of biosolids with rice straw significantly increased plant height, shoot, and root dry weight. Moreover, it promoted 100.51% dry matter production compared to control. But the dry matter was recorded 46.80% only in urea (þN) application. The highest vegetative growth and delayed drying of basal leaves were attained using 1/2 of compost with 1/2 amount of urea, of the optimal dose of nitrogen (N) requirement for corn production. The recorded heavy metals concentration in plant tissues was quite low. Most of the heavy metals in composts of biosolids were on average 30 times lower compared to the standard limit of municipal solid waste in the United States. The compost of biosolids with rice straw provided superior performance in corn growth compared to the compost of biosolids with sawdust. Both evaluated composts produced by solid-state bioconversion process were nonhazardous and did not contribute any detrimental effect or symptoms on corn growth and development. Simultaneously, it would behave as a potential sustainable environmentally friendly route of biosolids management and disposal as value added organic fertilizer for agronomic/horticultural use.